Sebaran Dan Keragaman Spasial Faktor-Faktor Yang Mempengaruhi Kemiskinan Di Kabupaten Tegal (Distribusi Dan Faktor Penyebab Kemiskinan Di Kabupaten Tegal) - Izatun Purnami; Ernan Rustiadi; Andrea Emma Pravitasari (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Poverty is one of the crucial social problems in Tegal Regency, Central Java Province. Specific solutions are needed in a particular area to effectively combat poverty. The purpose of this study is to identify the spatial distribution and pattern of poverty in Tegal Regency using Spatial Autocorrelation analysis (Moran’s Global Index & Local Indicator of Spatial Autocorrelation/LISA) and to determine the spatial diversity of factors that influence poverty in Tegal Regency using Geographically Weighted Regression analysis. The research results show the clustered spatial distribution and pattern of poverty in Tegal Regency, and there are various specific influences from each factor that affects poverty in each village/subdistrict in Tegal Regency. Keywords: Spatial Autocorrelations, Global Moran Index, LISA